PROTISTA: PROTOZOA ,CHARACTERISTICS, SCIENTIFIC SIGNIFICATION (Academicia Globe: Inderscience Research, 2023)
Protista, a diverse group of eukaryotic microorganisms, plays a crucial role in ecosystems as primary producers and consumers. This article explores the multifaceted ecological contributions of protozoa, including nutrient cycling, predator-prey interactions, and symbiotic associations. It underscores the significance of protozoa as microbial drivers of ecosystem dynamics and stability Protozoa, often overshadowed by larger organisms, are integral components of microbial communities that influence ecosystem processes. As predators, they regulate bacterial populations in aquatic ecosystems, preventing bacterial overgrowth. Their grazing activities influence nutrient cycling and carbon flow within food webs, impacting larger organisms up the trophic ladder. Additionally, some protozoa engage in mutualistic relationships with other microorganisms. For instance, ciliates like Paramecium host endosymbiotic algae (zoochlorellae), benefiting from photosynthetic products. These associations contribute to carbon and oxygen cycling in aquatic ecosystems Changes in protozoan communities can serve as indicators of environmental health. Shifts in protozoan diversity and abundance can signal pollution or disturbances in aquatic ecosystems. Monitoring protozoa can aid in assessing ecosystem integrity Protozoa also have significant implications for human health, as some species can cause diseases with wide-ranging impacts. For example, Plasmodium, a genus of parasitic sporozoans, is responsible for causing malaria, affecting millions of people worldwide. Similarly, the protozoan Trypanosoma causes sleeping sickness in Africa, while Balantidium coli can lead to dysentery. Giardia lamblia and Entamoeba histolytica are known to cause gastrointestinal infections. Advances in research have led to improved strategies for disease prevention and control